Analisis Faktor Penyebab Kesulitan Belajar Matematika Siswa Kelas VIII SMP Dwiguna Depok Tahun Ajaran 2023/2024 - Alviana Legista; Alya Nabila; Astri Astuti; Iif Nadiatul Ulumiah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The research is aimed at identifying factors that cause student failure in learning and the types of difficulties experienced by students. The subject of this study is an eighth grade high school student Dwiguna Depok. The data analysis technique used in this study is data reduction, i.e. concluding, separating important things that have already been obtained through the observation, interview and documentation stages of mathematical learning difficulties. This research includes a descriptive type with a qualitative approach. The results show that there are several factors that cause students difficulties in learning mathematics, including individual differences in mathematical ability, lack of motivation, inappropriate teaching methods, health or emotional disorders, and environmental factors.